ASSESSMENT AND EVALUATION AS A MEANS OF MOTIVATION FOR LEARNING A FOREIGN LANGUAGE (Journal of Science-Innovative Research in Uzbekistan, 2024)
The importance of control at different stages of learning a foreign language is emphasized. The need for objective assessment and marking during learning is substantiated, since there is a close relationship between assessment and the formation, maintenance and strengthening of motivation in mastering a foreignlanguage. It is concluded that an objective, comprehensive assessment is an important motivating stimulus for a student and an effective tool in a teacher’s arsenal